Dignity and the Founding Myth of Bioethics - Reis-Dennis, Samuel (The Hastings Center report, 2023)
In this article, I reject the “principlism” of Tom Beauchamp and James Childress and argue that respect for autonomy is, and ought to be, the fundamental value of bioethics. To do so, I offer a reconstruction of what I call the field's “founding myth,” a genealogy that affords primacy to the right to be respected as a human being with dignity. Next, I examine the relationship between this basic right and a derivative right of autonomy. I suggest that principlism has promulgated an uncharitable understanding of respect for autonomy, one that ensures that the principle cannot occupy the central position I claim for it. Finally, I sketch a more plausible understanding of respect for autonomy and explore its implications.